The Combination of Aquatic Species in Integrated Multi-Trophic Aquaculture with Paddy in Brackish Water: An Investigation of Feed Utilization Performance - Heriansah Heriansah; Indra Cahyono; Hamsiah Hamsiah (Universitas Gadjah Mada, 2023)
This study investigated the performance of artificial feed in the Integrated Multi Trophic Aquaculture (IMTA) system through a combination of milkfish, tiger shrimp, and clam involving paddy in brackish water. The three combination groups (C) and triplicate including milkfish and paddy (C-2), milkfish, tiger shrimp, and paddy (K-3), and milkfish, tiger prawns, clams, and paddy (C-4) were examinated for 80 days on a model sheeting pond designed to have a volume of 280 L and a density of 30 individuals. Meanwhile, 30 clumps of paddy were maintained through the floating method which is constructed from bamboo with an area of 1 m2. Feeding 3 times a day with 5% of biomass resulted a mean Feed Conversion Ratio (FCR) and Index Profit (IP) of 2.1 and 2.0 for C-2, 2.0 and 2.9 for C-3, and 1.9 and 3.1 for C-4, respectively. The results showed that the best trend pattern were the combination of C-3 species which were statistically found to have a significant effect (P<0.05) on FCR and IP performances. The findings of current study have practical significance for the expansion of co-culture of paddy and aquatic animals in brackish water which important by ecologically, biologically, and economically.